Comparative international management - Sorge, Arndt Michael; Koen, Carla; Noorderhaven, Niels G. (Abingdon, Oxon Routledge, Taylor & Francis Group, 2024)
"Comparative International Management is a classic textbook for International Business that teaches the core concepts of International Business through a systematic comparison of management practice in countries across the world. This approach, unique to textbooks in the field, highlights cultural and behavioural themes and demonstrate the diversity of practice in global business, and allows for an exploration of globalization. Fully revised and updated, this third edition has been restructured for clarity and ease of use, with new sections covering theoretical underpinnings so that they are easy to understand. Also new to this edition: Coverage of emerging and contemporary issues including environment and sustainability issues; international SMEs and entrepreneurship; technology, AI, and automation; and the future of work post-pandemic Practical application sections to help readers connect theory with practice More coverage of government and non-profit organizations Reflective and problem-solving questions at the end of each chapter With student and instructor friendly resources such as chapter summaries, mini-case scenarios, larger case studies and power-point slides, this book is essential core reading for advanced level and postgraduate students in International Business and International Management"--
1. Introduction to comparative international management -- 2. National cultures and management – the etic approach -- 3. National cultures and management – the emic approach -- 4. Institutional diversity and management -- 5. Integrating approaches -- 6. Comparative corporate governance -- 7. Managing resources: Operations management -- 8. Managing resources: Human resource management -- 9. Managing resources: National innovation systems -- 10. Multinational corporations: structural, cultural and strategic issues -- 11. Globalization: interdependencies, harmonization and societal specificity.
Includes bibliographical references and index.
Keywords: Comparative management; International business enterprises -- Management; Management -- Cross-cultural studies